FAKTOR PEMBENTUK HARAPAN WISATAWAN; SEBUAH PERSPEKTIF LINTAS BUDAYA (STUDI PADA WISATAWAN PERANCIS, AUSTRALIA, DAN NUSANTARA YANG BERKUNJUNG DI PULAU LOMBOK) - Rinuastuti, Baiq Handayani (Jurnal Magister Manajemen, 2016)
This research aimed to determine the modifier factors of the Australian, France and Indonesian (Nusantara) tourist hope toward Lombok Island, and explain the relation between cultural background of each group according to Hofstede theory and the modifier factors. Method that used in this research was descriptive method with the sample survey approach. Sample for each group was 50 persons. The data were analyzed by descriptive analyze and statistic analyze by using factor analyze. The result shown the Australian with have individualistic culture background was forming the hope dominated by past experience, the France tourist, with uncertainty avoidance culture background, was forming their hope by collecting external information, while Indonesian with their collectivities culture tend to form their hope base on word of mouth. The difference of hope modifier in each tourist group became important thing to payed by the tourist executants to determine the tourism marketing strategy in the future. Keywords : Hope, Hofstede Culture, Past Experience, External Information, Destination Image, Word of Mouth